Overexpression of LncRNA SNHG14 as a biomarker of clinicopathological and prognosis value in human cancers: A meta-analysis and bioinformatics analysis - Liu, Bin; Lu, Tingting; Wang, Yongfeng; Zhang, Guangming; Fu, Liangyin; Yu, Miao; Yang, Kehu; Cai, Hui (Frontiers in Genetics, 2022)
Background: SNGH14 is a newly discovered long non-coding RNA (lncRNA) highly associated with tumorigenesis. However, whether the level of SNHG14 is related to the prognosis of patients with different cancer types is unclear. Methods: PubMed, Web of Science, Cochrane Library, and Embase were searched to identify eligible studies from inception to November 2021. The odds ratio (OR) and 95 % confidence interval (CI) were utilized to analyze dichotomous variables, while the hazard ratio (HR) and 95 % CI were used for survival outcomes. We also included trial sequential analysis (TSA) to assess whether the current evidence was sufficiently conclusive. Stata 15.0 and TSA 0.9 software were used for data analyses. Results: A total of 21 studies involving 1,080 patients, mainly from China, were included. Our results revealed that high SNHG14 expression was associated significantly with poor overall survival (OS) (HR = 1.39; 95% CI:(1.06 to 1.83); P = 0.017). In addition, elevated SNHG14 expression was related to tumor size (>3.5cm) (OR = 1.60; 95% CI: (1.20 to 2.14); P = 0.001), TNM staging (OR = 0.54; 95% CI:(0.40 to 0.71); P <0.001), lymph node metastasis (OR = 1.86; 95% CI:(1.35 to 2.55); P <0.001), differentiation grade (OR = 1.95; 95% CI: (1.36 to 2.80); P <0.001), and distant metastasis (OR = 2.44; 95% CI:(1.30 to 4.58); P = 0.005). However, no significant difference was observed between age (OR = 0.98; 95% CI:(0.72 to 1.35); P = 0.915) and gender (OR = 0.98; 95% CI:(0.72 to 1.35); P = 0.915) from the enhanced expression of SNHG14. Conclusion: The current study revealed that overexpression of SNGH14 is associated with low OS rate and clinicopathological characteristics. SNGH14 can be a novel tumor marker that aids in tumor diagnosis, thereby improving patient prognosis.